Quality Evaluation of Set Yoghurt Produced by Two Factories in Khartoum State, Sudan - Abdalla, Mohamed Osman Mohamed; Adam, Ismael Mohammed Abdalla (University of Khartoum Journal of Agricultural Sciences, 2025)
This study was carried out to chemically and microbiologically evaluate set yoghurt produced by two factories (F1 and F2) in Khartoum State. Ninety samples (45 from each factory) were collected and chemically and microbiologically analyzed at 1, 5 and 10 day intervals. The results showed that fat and total solids contents and titratable acidity were higher in F2 than in F1, while protein and solids-non-fat contents were higher in F1. Lacobacillus bulgaricus, coliform bacteria and yeasts and moulds counts were higher in F1. During storage, fat content increased in F1 and decreased in F2, while protein content increased in F1 and followed an irregular pattern in F2. Total solids and solids-non-fat contents increased till day 5, and then decreased at the end of the storage period in the two factories, while titratable acidity steadily increased towards the end in the two factories. Lactobacillus bulgaricus count increased till day 5 then decreased towards the end in both factories, while coliform bacteria and yeasts and moulds counts increased towards the end.